Parsonage-Turner Syndrome Revisited: Four Case Reports and Literature Review - Monteiro, Sara; Silva Gomes, Diogo; Moura, Nuno; Sarmento, Marco; Cartucho, António (Gazeta Médica, 2022)
INTRODUCTION: Parsonage-Turner syndrome is a rare disease characterized by acute and severe shoulder pain followed by upper extremity paralysis, that is severely underdiagnosed in clinical practice. The objective is to describe four illustrative clinical cases and provide a summary review of the topic. CASE REPORTS: Four patients (aged 56 to 84 years-old) diagnosed with Parsonage-Turner syndrome were followed up for functional recovery and patient satisfaction after conservative treatment. Despite presenting with typical sudden-onset pain in the shoulder region, followed by weakness in the shoulder/arm, all patients had delayed diagnosis. Only one patient reported a preceding viral infection, which is the most common trigger. Pain subsided after 3-8 days, but shoulder/arm weakness persisted. All patients recovered, totally or partially, with pain management and physical therapy. Recovery took 6-15 months and was monitored through clinical evaluation and electromyography. At last follow-up, all patients were satisfied. CONCLUSION: Parsonage-Turner syndrome has a higher incidence than previously assumed and is frequently underdiagnosed. It must be considered in the differential diagnosis of the painful shoulder, especially if muscle weakness is present. Despite being a self-limited condition, recovery is usually slow, and a prompt diagnosis is key for patient’s reassurance and starting adequate supportive treatment.